Possible correlation of electrochemiluminescence based numerical cut off index value with concentration of anti-SARS-CoV-2 antibody: Is it worth reporting? - Shabnum Khawaja; Mohammad Asif; Samina Naz Mukry; Tahir Sultan Shaamsi (SAGE Publishing, 2021)
Background: Many laboratories are reporting a numerical cutoff index value (COI) value for most anti-SARS-CoV-2 qualitative tests. These numerical values in patients' report ultimately created great confusion in the public and physicians, therefore this study was designed to evaluate the correlation of electrochemiluminescence (ECLIA) based numerical COI values with quantitative ELISA of anti-SARS-CoV-2 antibody. Design and Methods: Two hundred and twenty-eight (228) recovered COVID-19 patients were included; their serum samples were analyzed by quantitative ELISA and ECLIA for anti-SARS-COV-2 antibodies. Results: One hundred and seventy-three (75.8%) patients tested positive by ECLIA and ELISA assay and thirty-seven (6.2%) were tested negative by both methods. A weak positive correlation (r=0.37) was found between numerical COI value of ECLIA with ELISA concentration, which was statistically significant with p<0.001. All values were dispersed on scatter plot and there was no significant linear relationship between ECLIA and ELISA assay. Conclusions: As both testing techniques are base upon the same immunological phenomena of detecting antibodies against nucleocapsid protein. We suggest that COI values are not meant to describe the immunity level of the individuals thus the physicians should not consider it as a quantitative value for antibody levels in COVID-19 patients.